Exchange Rate Fluctuations, Inflation and Industrial Output in Nigeria - Okafor Tochukwu; Esther Adegbite; Babajide Abiola (International Journal of Supply Chain Management, 2018)
Over the last 50 years, Nigerias industrial sector has declined considerably in both productivity and contribution to economic growth in the country. Empirical evidence suggests that exchange rate fluctuations and rising inflation has impeded industry output growth in the country. This study examines the effect of exchange rate fluctuations and inflation on industrial output in Nigeria. The study covers the period between 1981Q1 and 2015Q4. The study adopted the SVAR econometric technique to analyses the impact of a shock to the independent variables on industry output. The study found that a positive shock to exchange rate has a negative impact on output growth and that a positive shock to inflation has a temporal negative effect on output and becomes positive after the fourth quarter. The forecast error variance decomposition technique showed that exchange rate and inflation account for about 2.6 percent and 10 percent of variations in industry output respectively. The study recommends that take aggressive steps to reduce exchange rate volatility and ensure price stability in the country through effective control of money supply in order to boost industry sector performance in Nigeria.